Perspective of Principals on Different Aspects of Counselling Services in Delhi Schools: Exploring the Perspective of Delhi School Principals on Counselling Services (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Over the last few decades in India, counselling has emerged as a professional field throughout the 29 states and has generated a lot of attention from various stakeholders, particularly from the principals who have devoted time to explore its utility for school going children. The principal facilitates interaction between various groups within the school and extends the scope of these ancillary services to even cover the parents and a number of agencies outside the school system. It was therefore, felt important to know as to what was their opinion about the counselling programme of their schools. Descriptive survey method was used as a research design for the study. The target population of the study was the principals overlooking different government and private schools of Delhi. Sample of 56 principals were randomly selected out of a total of seven districts of the capital of India. This research paper highlights their perspective on various aspects associated with counselling programmes in Delhi.